Semi-empirical estimates of stratospheric circulation and the lifetimes of chlorofluorocarbons and carbon tetrachloride - Stephen Bourguet; Kane Stone; Megan Lickley (Communications Earth & Environment)
Abstract Chlorofluorocarbons (CFCs) and carbon tetrachloride (CCl4) are ozone-depleting substances with high radiative efficiencies; however, uncertainties in their atmospheric lifetimes hinder top-down emission monitoring efforts. Here, we compute the loss, emission, and lifetime of CFC-11, CFC-12, and CCl4 using their mass balance in the stratosphere. We first infer the strength of the stratospheric overturning circulation using satellite measurements of nitrous oxide; the mass flux at about 18 km is then used to compute the loss of CFC-11, CFC-12, and CCl4. We confirm that anomalous surface measurements of CFC-11 from 2013 to 2018 cannot be attributed to variability in stratospheric transport alone, and we infer near-steady CCl4 emissions since 2013. Atmospheric lifetimes (50, 86, and 41 yr) independent of previous work are also computed using loss rates. These estimates add confidence to emission inversions and projections of the compounds’ ozone and climate impacts, and may help detect breaches of the Montreal Protocol.